Language and culture in English for business purposes: noticing their importance through television advertisements - Rashid Ali, Farrah Diebaa; Ahmad, Farrah (UTM Malaysia, 2013)
This study aimed to look at the awareness of Malaysian English for Business Purposes (EBP) students on the importance of using appropriate language in relation to cultural differences in an international business setting. This research was conducted as a result of several stressful hours of restating and reinforcing the importance of understanding cultural differences in written and spoken business communication to the EBP learners. Prior to the study, the students failed to see that the world communities are built of general and personal cultures. The term culture and subculture did not really bother them as they were not able to see what culture constitutes of. Hence, miscommunication caused by cultural bias was often seen in their outcomes. However, once they were able to notice the different cultural elements presented in the nine culturally-embedded television advertisements, it has been observed that the students were more sensitive towards their selection of words, phrases, sentence structures and their written or spoken styles. They were more careful when using vernacular language, idioms, over-generalization and under-generalization words. Reducing the number of miscommunication possibilities caused by wrong selection of words, phrases and written or spoken styles is crucial. Thus, by arriving at such conclusion, it can be assumed that now the students have realized the important roles played by both language and culture in EBP settings